Antithrombotic pretreatment increases very-early mortality in primary intracerebral hemorrhage. (28th February 2017) - Roquer, Jaume; Vivanco Hidalgo, Rosa María; Ois, Angel; Rodríguez Campello, Ana; Cuadrado Godia, Elisa; Giralt Steinhauer, Eva; Gómez González, Alejandra; Soriano-Tarraga, Carolina; Jiménez Conde, Jordi
Abstract : Objective: To analyze the effect of previous antiplatelet (AP) and vitamin K antagonist (VKA) treatments on outcome in patients with primary intracerebral hemorrhage (ICH). Methods: In this prospective observational study, we analyzed 529 patients according to antithrombotic pretreatment: none, AP, or VKA. Very-early (24-hour) death, 3-month mortality, and functional independence were analyzed. Results: Of 236 (44.6%) pretreated patients, 147 (27.8%) patients were taking AP and 89 (16.8%) VKA. Very-early death was observed in 13.4% and was increased in pretreated patients: 19.0% for AP and 27.0% for VKA treatment, compared to 6.5% in non-pretreated patients, p < 0.0001. Three-month mortality was 40.8% overall (49.7% for AP pretreated, 58.4% for VKA pretreated, and 31.1% for non-pretreated patients, p < 0.0001). The adjusted odds of very-early and 3-month mortality were 2.55 ( p = 0.004) and 1.56 ( p = 0.046) for AP-pretreated patients and 4.24 ( p < 0.0001) and 2.34 ( p = 0.01) for VKA-pretreated patients, respectively, compared with non-pretreated patients. The effect of antithrombotic pretreatment on mortality from 24 hours to 3 months was nonsignificant. At 3-month follow-up, 28.5% of patients remained functionally independent: 22.4% of AP-pretreated, 15.7% of VKA-pretreated, and 35.5% of non-pretreated patients ( p < 0.0001). Conclusions: A high percentage of patients with ICH preventively treated with VKA or AP died during the first 24 hours after admission. Both treatments were predictors of very-early mortality. The final effect of antithrombotics on 3-month mortality remains significant through its strong effect on very-early mortality. Safety concerns about starting chronic antithrombotic treatment should be considered not only when VKA treatment is planned but also for AP treatment.